ANALISIS PENGARUH KEPERCAYAAN MEREK DAN KUALITAS PRODUK TERHADAP LOYALITAS KONSUMEN LAPTOP DI KOTA SEMARANG - Erna Dwi Astuti, 10.05.51.0034; Kasmari, Kasmari (Students Journal of Economic and Management, 2014)
The development ofcomputer technologyhasbroughtmanychanges to theportablecomputerorthelaptop. The designs aregetting sleeker, lighterweightandmorepower-savingcapabilitiesbecomean important part inthe development ofnextlaptop. Consumersalsoconsider the brandandthe quality ofthe product purchasedin orderto satisfyandas desired.This study aimed to analyze the effect of brand trust variables and product quality to customer loyalty. The sample usedinthis study were100respondentsto thesamplingtechniqueisthemethod ofpurposive sampling, namely samplingof carefully selectedby taking the objectof researchisselectiveandhasspecificcharacteristics. The data usedisprimary data, analysisof dataused includetest validity, reliability test, normality test,linear regression, the coefficientof determinationandtesthypothesesincludethe F testand t test. Based on data analysis and hypothesis testing showed that in partial trust the brand (X1) and a significant positive effect on consumer loyalty (Y) laptop. The variable quality of the product (X2) is not positive and significant effect on customer loyalty (Y) laptop. Variables trust the brand and quality products together positive and significant effect on consumer loyalty laptop. Test results of determination known brand trust variables and product quality can explain the variation of 33.8% on consumer loyalty while the remaining 66.2% is influenced by other variables that were not analyzed in this study. Keywords: Brand Trust, ProductQualityandConsumer Loyalty